Acquired von Willebrand syndrome in patients with ventricular assist device or total artificial heart - Heilmann, Claudia; Geisen, Ulrich; Beyersdorf, Friedhelm; Nakamura, Lea; Benk, Christoph; Berchtold-Herz, Michael; Trummer, Georg; Schlensak, Christian; Zieger, Barbara (Thrombosis and Haemostasis, 2010)
Unexplained bleeding episodes are associated with ventricular assist devices (VAD) and can occur in part due to acquired von Willebrand syndrome (AVWS). AVWS is characterised by loss of high molecular weight (HMW) multimers of von Willebrand factor (VWF) and decreased ratios of collagen binding capacity and ristocetin cofactor activity to VWF antigen. Loss of multimers can occur as VWF is subjected to increased shear stress, which occurs in presence of VADs. We studied 12 patients who required mechanical support of their native heart for terminal cardiac insufficiency. Nine patients underwent placement of a VAD, while three underwent placement of a total artificial heart (TAH), which is connected directly to heart and large cardiac vessels without cannulas. Within one day of VAD implantation, four of five patients evaluated demonstrated loss of HMW multimers and impaired VWF function. AVWS was present within two weeks of implantation in eight of nine patients, and in all seven tested patients after ≥3 months. Patients with different VAD types developed varying severities of AVWS. After VAD ex-plantation, HMW multimers were detectable and VWF function normalised in all patients. AVWS was not observed in the TAH patients studied. Our findings demonstrate that patients with an implanted VAD experience a rapid onset of AVWS that is quickly and completely reversed after device explantation. In addition, TAH patients do not develop AVWS. These results suggest that shear stress associated with exposure of blood to VAD cannulas and tubes may contribute to the development of AVWS.
Keywords: Acquired coagulation disorders; von Willebrand disease; surgery